Suggested Issues for Discussion - CADE, Conselho Administrativo De Defesa Econômica (Revista do IBRAC, 2025)
In every country that makes a serious commitment to the development of a market economy, privatisation of state-owned enterprises has a high priority. There is an obvious tension in the privatisation process, however, between the desire of the state to obtain the highest possible price for the privatised assets, on the one hand, and the need for the creation of efficiency-enhancing, competitive markets, on the other.